Alasan untuk memilih kerja di daerah tertinggal: studi kualitatif terhadap dokter lulusan Universitas Cendana Kupang (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Medical graduate career choice in the underserved area: a qualitative study in Nusa Tenggara TimurPurpose: Although many government policies have been directed toward rural workforce shortage, little attention was given to meet medical graduates’ needs other than financial. This study explored the internal reasons why medical graduates chose the rural area as a place to work.Methods: Three focussed group discussion (FGD) with phenomenology approach followed by a total of 24 medical graduates recruited purposively and work in three islands and six districts in Nusa Tenggara Timur Province. Interview transcripts were analyzed thematically by two researchers.Results: First, interventions which have been done and proven to support the recruitment of medical graduates to underserved area were: contract bound scholarship; incentives and work load calculation; improvement of facilities, security, and accessibility of underserved areas; and promotion of underserved areas as tourism sites. Second, the process of medical graduates recruitment in Indonesia (internship, PTT, and Nusantara Sehat) has considered several important things: rural origin and has friends/colleagues in destination area (proven by submitting local authority recommendation). Third, new issues added by this study are locations supporting autonomy and providing opportunities and supervisors for further learning, including conducting research, will be given priorities. Half of the respondents (12 out of 24) explicitly stated that they chose a place where they can learn more about the medical specialty of interest. Even four out of those 12 respondents stated further that they chose a place where they can conduct research under specialist supervision for the medical specialty of interest.Conclusions: This study adds that the graduates’ choice of workplace which provides opportunities for further learning and conducting research under specialist supervision needs further attention. Local authorities are suggested to invest in IT facilities to support tele-supervision and collaborate with local medical school to adapt the concept of rural clinical school which has been widely established throughout Australia. Second, the placement areas for Specialist Compulsory Work (Wajib Kerja Dokter Spesialis) Program and other similar programs can be expanded and prioritized for underserved rural hospitals to provide clinical supervisors and support the recruitment of medical graduates to those underserved areas.